Comparative investigation on soil salinity leaching under subsurface drainage and ditch drainage in Xinjiang arid region - Xinlin, He; Hongguang, Liu; Jianwei, Ye; Guang, Yang; Mingsi, Li; Ping, Gong; Aimaiti, Aernaguli (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: This study was carried out to explore the effects of leaching salinity under subsurface drainage and mulched drip irrigation on saline and alkaline land from the year 2012 to 2014in Xinjiang Region of China. Three sampled points were both set up in the subsurface drainage and ditch drainage areas. Soil samples were obtained at varied depths. Through observing the underground water table under each sampled point and measuring the electrical conductivity (EC) of the soil extracts, the following results were obtained: (1) after draining, the underground water table ranged from 1.6 m to 2.2 m in the ditch drainage area, and ranged from 1.5 m to 2.2 m in the subsurface drainage area. Thus, both irrigations could control underground water table below 1.5 m which is deeper than the main water-absorbing layers of crop root systems; (2) for subsurface drainage, the closer to the pipe, the better to leach salinity; decreased from the initial 13.54-22.95 g/kg to 8.20- 11.47 g/kg; (3) compared with the amounts in 2012, soil total salt at each sampling point at depths of 0-200 cm in subsurface drainage area decreased by 42.99%, 36.84% and 24.41% respectively in 2014; and in ditch drainage area decreased by 46.85%, 38.12% and 30.80% respectively in 2014. The results showed both ditch and subsurface drainage could leach salinity effectively.Keywords: mulched drip irrigation, soil salinity, subsurface drainage, ditch drainageDOI: 10.3965/j.ijabe.20160906.2441Citation: He X L, Liu H G, Ye J W, Yang G, Li M S, Gong P, et al. Comparative investigation on soil salinity leaching under subsurface drainage and ditch drainage in Xinjiang arid region. Int J Agric & Biol Eng, 2016; 9(6): 109－118.